Risk Factors Associated with Diabetic Ketoacidosis at the Onset of Type 1 Diabetes Mellitus - Kansakar, Prerana; Shrestha, Shrijana; Paudyal, Buddhi Prasad; Prajapati, Alisha; Shrestha, Narottam (Journal of Nepal Health Research Council, 2022)
Background: There are various factors which increase the risk of diabetic ketoacidosis at the onset of type 1 diabetes mellitus. There have not been any such studies in our setting. This study was done to find the prevalence and risk factors associated with the development of diabetic ketoacidosis at onset of type 1 diabetes mellitus. Methods: Children and young adults with type 1 diabetes mellitus being treated at Patan hospital were approached and after obtaining an informed consent, all the patient information on various risk factors for diabetic ketoacidosis were collected in a pre-developed proforma. Data was entered in Microsoft Excel and analysis was done using statistical package for the social sciences-16. Ethical approval was taken from Institutional Review Committee- Patan Academy of Health Sciences. Results: Out of 99 patients with type 1 diabetes enrolled in the study, 52.5% presented in diabetic ketoacidosis at the onset. The duration of symptoms was significantly less in patient presenting with diabetic ketoacidosis than without diabetic ketoacidosis (6.45±7.57 vs 9.13±10.12, p=0.04). There was no significant difference in the mean age, mean glycosylated hemoglobin, mean body mass index, gender, parents’ literacy and medical consultations prior to diagnosis. Conclusions: More than half of the patients with type 1 diabetes presented in diabetic ketoacidosis. The shorter duration of symptoms prior to presentation was the only significant factor leading to presentation as diabetic ketoacidosis. Keywords: Diabetic ketoacidosis; risk factors; type 1 diabetes mellitus.